The Serine/Threonine Kinase STK11 Promotes Shigella flexneri Dissemination through Establishment of Cell-Cell Contacts Competent for Tyrosine Kinase Signaling - Dragoi, Ana-Maria (Infect Immun, 2014)
Shigella flexneri is an intracellular pathogen that disseminates in the intestinal epithelium by displaying actin-based motility. We found that although S. flexneri displayed comparable actin-based motilities in the cytosols of HeLa229 and HT-29 epithelial cell lines, the overall dissemination process was much more efficient in HT-29 cells. Time-lapse microscopy demonstrated that as motile bacteria reached the cell cortex in HT-29 cells, they formed membrane protrusions that resolved into vacuoles, from which the bacteria escaped and gained access to the cytosol of adjacent cells. In HeLa229 cells, S. flexneri also formed membrane protrusions that extended into adjacent cells, but the protrusions rarely resolved into vacuoles. Instead, the formed protrusions collapsed and retracted, bringing the bacteria back to the cytosol of the primary infected cells. Silencing the serine/threonine kinase STK11 (also known as LKB1) in HT-29 cells decreased the efficiency of protrusion resolution into vacuoles. Conversely, expressing STK11 in HeLa229 cells, which lack the STK11 locus, dramatically increased the efficiency of protrusion resolution into vacuoles. S. flexneri dissemination in HT-29 cells led to the local phosphorylation of tyrosine residues in protrusions, a signaling event that was not observed in HeLa229 cells but was restored in STK11-expressing HeLa229 cells. Treatment of HT-29 cells with the tyrosine kinase inhibitor imatinib abrogated tyrosine kinase signaling in protrusions, which correlated with a severe decrease in the efficiency of protrusion resolution into vacuoles. We suggest that the formation of STK11-dependent lateral cell-cell contacts competent for tyrosine kinase signaling promotes S. flexneri dissemination in epithelial cells.